Fostering Social Harmony: The Impact of Islamic Character Education in Multicultural Societies - Salsabila Anita Firdaus; Suwendi Suwendi (AL-ISHLAH: Jurnal Pendidikan, 2025)
In multicultural societies, fostering social harmony requires educational approaches that integrate values of tolerance, respect, and mutual understanding. This study examines the role of Islamic-based character education in shaping individuals who can navigate diversity dynamics, balancing Islamic values with modern societal needs. This research employs a qualitative literature review method, analyzing data from various credible sources, including scientific journals, books, and articles. The study systematically reviews and synthesizes findings to assess the impact of Islamic character education on promoting social harmony in multicultural contexts. The analysis reveals that Islamic-based character education serves as a crucial foundation for character development in multicultural societies. It emphasizes core values such as tolerance, respect, and empathy, enabling students to appreciate diversity and coexist peacefully. Islamic character education fosters an inclusive mindset, encouraging children to respect differences and actively contribute to social cohesion. While Islamic-based character education effectively supports social harmony, the study identifies the need for strategies to address future challenges, including resistance to diversity, globalization pressures, and the potential marginalization of minority groups. A holistic, collaborative approach—combining educators, policymakers, and communities—is recommended to enhance the effectiveness of character education programs. Ultimately, strengthening Islamic character education not only fosters social harmony but also equips the younger generation with the resilience and ethical grounding to face global challenges in an increasingly diverse world.